1984
DOI: 10.1002/art.1780271203
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral 1,25‐dihydroxyvitamin D and calcium on glucocorticoid‐induced osteopenia in patients with rheumatic diseases

Abstract: Twenty-three rheumatic disease patients with glucocorticoid-induced osteopenia (defined by measurement of forearm bone mass) completed an 18-month double-blind, randomized study to assess the effect of oral calcium and 1,25-dihydroxyvitamin D ( 1,25-OH2D) or calcium and placebo on bone and mineral metabolism. Intestinal 47Ca absorption was increased (P < 0.05) and serum parathyroid hormone levels were suppressed (P < 0.01) by 1,25-OH2D (mean dose 0.4 pgl day); however, no significant gain in forearm bone mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
2
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(45 citation statements)
references
References 29 publications
1
40
2
2
Order By: Relevance
“…A total of 88 RCTs were identified by this means. A further eight relevant trials were identified from the reference lists of identified trials and relevant review articles, [61][62][63][64][65][66][67][68] and an additional four by hand-searching only. [69][70][71][72] No trials were identified by pharmaceutical companies that had not been identified by other means.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 88 RCTs were identified by this means. A further eight relevant trials were identified from the reference lists of identified trials and relevant review articles, [61][62][63][64][65][66][67][68] and an additional four by hand-searching only. [69][70][71][72] No trials were identified by pharmaceutical companies that had not been identified by other means.…”
Section: Search Resultsmentioning
confidence: 99%
“…63,64,[117][118][119][120][121][122][123] These trials included those in which patients in both the intervention and control groups received calcium and/or vitamin D in comparable doses. Those studies in which vitamin D derivatives were compared with another active intervention are discussed later (page 36).…”
Section: Vitamin D Derivativesmentioning
confidence: 99%
“…The finding of calcium stones and the increased risk of urolithiasis in patients treated with glucocorticoids suggest that the mechanism of stone formation is steroid-induced bone demineralization followed by hypercalciuria. [8][9][10][11][12][13] Risk factors for recurrence…”
Section: Composition Of Stonesmentioning
confidence: 99%
“…7 However, in the setting of glucocorticoid therapy, vitamin D and calcium supplementation may cause hypercalcemia [8][9][10] and increased urinary calcium excretion with consequent risk for urolithiasis. [11][12][13] Little is known about the incidence, timing, and causes of urolithiasis in children with ALL and the composition of stones. In this study, we define the incidence, timing, clinical consequences, risk factors, and outcome of urolithiasis, as well as the stone composition in children with ALL.…”
Section: Introductionmentioning
confidence: 99%
“…1 These recommendations are based on the safety profile of moderately dosed calcium and vitamin D and studies demonstrating that (1) oral glucocorticoids can lead to rapid bone loss within the first 3 months of glucocorticoid use, 2 and (2) while the risk of GIOP increases with the cumulative glucocorticoid dose, there is no dose of glucocorticoids that does not accelerate bone loss or increase fracture risk; 3,4 (3) several randomized controlled trials have shown that the administration of calcium and vitamin D in patients undergoing glucocorticoid therapy can prevent early bone loss. [5][6][7] In contrast, recommendations regarding the use of bisphosphonates are individualized based on risk factors and childbearing potential.…”
Section: Introductionmentioning
confidence: 99%